Leaf number and plant height of three Canna x generalis cultivars - Zsiláné-André, A.; Somogyi, A.; Holb, I. (International Journal of Horticultural Science, 2017)
The aim of this three-year study was to evaluate the effect of three treatments (thiophanate methyl, charcoal dust, and control) on leaf number and plant height on three Canna x generalis cultivars (City of Portland, Richard Wallace and Robert Kemp). Results showed that the 3-year means of leaf number ranged from 13.9 to 23.1 for the three cultivars. The largest leaf numbers were for cultivar Robert Camp (23.1 in 2010) and the lowest for cultivar City of Portland (13.9 in 2011). Thiophanate methyl treatment produced the highest number of leaves and the values were significantly different at P< 0.05 from the control for all years and for all cultivars. Numbers of leaves in charcoal dust treatments were larger than the control treatments but it was not significantly different. Results on plant height ranged from 69.2 to 160.5 cm for the three cultivars. The largest plant height was for cultivar Robert Kemp (160.5 cm in 2011) and the lowest for cultivar City of Portland (69.2 cm in 2011). Thiophanate methyl treatment produced the highest plant height and the values were significantly different at P< 0.05 from the control for all years and for all cultivars. Plant heights in charcoal dust treatments were larger than the control treatments but it was not significantly different.